The Bahamas : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides the details of the IMF's projections and estimates on The Bahamas's basic data; generation and sale of electricity, value of construction starts and completions in the real sector; summary of operations of the nonfinancial public sector, central government revenue and expenditure, summary central government operations in the fiscal sector; summary accounts of the financial system, accounts of the central and commercial banks and other local financial institutions, selected interest rates in the monetary sector; balance of payments, comparative real exchange rates in the external sector, and so on.